Mathematical concepts and cultural values in guest reception traditions: an ethnomathematic study of the Dawan Tribe Community on The Timor Island - Bantaika, Aris; Son, Aloisius Loka; Ndapa Deda, Yohanis; Garcia-Garcia, Javier (Universitas Terbuka, 2025)
The aim of this study is to explore mathematical concepts and cultural values in the reception traditions of the Dawan tribe (Atoni Meto). The research method used is qualitative research with an ethnographic approach. The research subjects were three informants and the research objects were music, dance and handicrafts. The instruments used in this research were observation, interviews and documentation. The results of the research show that (1) there are mathematical concepts in the arts of music, dance and handicrafts in the reception traditions of the Atoni Meto tribe, including; flat shapes (Square, Circle, Rectangle, Rhombus, Triangle), spatial shapes (Cone, Cylinder and Cuboid), the Concept of Lines and Sets, and (2) Cultural values contained in hitting the gong (Leku Sene) namely as a guide and a sign of joy, dancing (Sbo'ot) symbolizes joy, traditional speech (Natoni) as a form of respect and continuity of bond, repetition as a sign of brotherly bonds, eating betel-nut (M'pua) as unity and a sign of conveying goals and eating together as unity.